A Escola de Química de Sergipe : o processo de formação de um campo profissional (1948-1967) - Conceição, Claudileuza Oliveira da (2010)
This study discuss the path for higher education in Chemistry, from the creation of the Instituto de Química Industrial (Industrial Chemistry Institute) and Escola de Química de Sergipe (Chemistry School of Sergipe), in order to show the process of formation and legitimation of the field of Chemistry in Sergipe. The timeframe is from 1948 to 1967. However, the work makes some setbacks in the timeline trying to expose the evidences left on the first experience. That Sergipe had with the teaching of chemistry in 1925. The theoretical framework chosen was the work of French sociologist Pierre Bourdieu. The logic of Bourdieu's thought is given to the theory of fields of training. In this study we worked with categories: field, scientific capital and habitus. We used different resources such as: laws, decrees, regulations, governmental messages and speeches, reports, books for the term of graduation, diplomas register book and daily spot, photographs, vintage newspapers and oral testimony. This study proposes a reflection on the educational, social, industrial and technological landscape of Sergipe and it intends to be a contribution to the field of studies of the History of Education in Sergipe lands.